Preventive and chronic mineralocorticoid receptor antagonism is highly beneficial in obese SHHF rats. (26th April 2016) - Youcef, G; Olivier, A; Nicot, N; Muller, A; Deng, C; Labat, C; Fay, R; Rodriguez‐Guéant, R‐M; Leroy, C; Jaisser, F; Zannad, F; Lacolley, P; et al.
Abstract : Background and Purpose: Mineralocorticoid receptor (MR) activation contributes to heart failure (HF) progression. Its overactivity in obesity is thought to accelerate cardiac remodelling and HF development. Given that MR antagonists (MRA) are beneficial in chronic HF patients, we hypothesized that early MRA treatment may target obesity‐related disorders and consequently delay the development of HF. Experimental Approach: Twenty spontaneously hypertensive HF dyslipidaemic obese SHHF cp/cp rats and 18 non‐dyslipidaemic lean SHHF +/+ controls underwent regular monitoring for their metabolic and cardiovascular phenotypes with or without MRA treatment [eplerenone (eple), 100 mg∙kg −1 ∙day −1 ] from 1.5 to 12.5 months of age. Key Results: Eleven months of eple treatment in obese rats (SHHF cp/cp eple) reduced the obesity‐related metabolic disorders observed in untreated SHHF cp/cp rats by reducing weight gain, triglycerides and total cholesterol levels and by preserving adiponectinaemia. The MRA treatment predominantly preserved diastolic and systolic functions in obese rats by alleviating the eccentric cardiac hypertrophy observed in untreated SHHF cp/cp animals and preserving ejection fraction (70 ± 1 vs. 59 ± 1%). The MRA also improved survival independently of these pressure effects. Conclusion and Implications: Early chronic eple treatment resulted in a delay in cardiac remodelling and HF onset in both SHHF +/+ and SHHF cp/cp rats, whereas SHHF cp/cp rats further benefited from the MRA treatment through a reduction in their obesity and dyslipidaemia. These findings suggest that preventive MRA therapy may provide greater benefits in obese patients with additional risk factors of developing cardiovascular complications.